A criação da área de proteção ambiental Cabuçu - Tanque grande em Guarulhos (2004-2010) - Araujo, Andre Luiz De [UNIFESP] (2019)
This paper deals with an analysis from an environmental history perspective, the elaboration of Law no. 6.798, of December 28, 2010; Draft Law no. 418/2009, authored by the Municipal Executive of Guarulhos, which resulted in the creation of the Cabuçu - Tanque Grande Environmental Protection Area. This dissertation addresses a number of issues related to the APA - Area of Environmental Protection within the scope of public policies, and at the same time, understands that the creation of an APA is at the same time the result of a long interaction between social formations and its natural surroundings, a legal intervention on a determined biophysical reality, and a space of disputes between diverse interests and perceptions about those natural areas. It is the para-doxo between the development and preservation to which it is inserted that give histo- ricity to the creation of a protected natural area, which in turn, refer to the relations between State and Society and Environment. And the incorporation of this inte- raction into the study of public policies aimed at environmental protection will re- sult in new laws.